Antifungal Activity of Aqueous and Ethanolic Leaf Extracts of Cassia Alata Linn - Timothy SY, Wazis CH, Adati RG, Maspalma ID (Journal of Applied Pharmaceutical Science)
Cassia alata Linn is an important medicinal plant as well as ornamental flowering plant. The leaf decoction of Cassia alata has been used to treat infectious diseases in north eastern Nigeria. This study was embarked upon so as to evaluate the safety and efficacy of Cassia alata in the management of fungal infectious diseases. The leaves of the plant were collected, dried and extracted using water and 95% ethanol. The extracts were used for evaluating antifungal activity against five clinical isolates of pathogenic fungi. The result of this study showed a dose dependent antifungal activity of both aqueous and ethanolic leaf extracts on the five selected clinical isolates of pathogenic fungi. The extracts inhibited the growth of Candida albicans, Microsporum canis and Trichophyton mentagrophyte better than the ketoconazole 200 mg used as a positive control (p
Keywords: Antifungal,Aqueous,Ethanol,Cassia alata.